Trade of Lithuanian dairy products and vertical relationship at the stage of distribution - Heinrich Hockmann; Angelė Kėdaitienė (Ekonomika, 2002)
This paper focuses on the theory of vertical co-ordination and its application to agriculture and the dairy industry. More specially, the paper analyses the distribution of Lithuanian dairy products in both the domestic and international market. The domestic retail system and tendencies in dairy product foreign trade are surveyed in this paper as well.
Keywords: 330; transaction; vertical co-ordination; retail system; foreign trade; dairy products